Dexmedetomidine Reduced Cytokine Release during Postpartum Bleeding-Induced Multiple Organ Dysfunction Syndrome in Rats - Liu Xianbao; Zhan Hong; Zeng Xu; Zhang Chunfang; Chen Dunjin (Mediators of Inflammation)
Dexmedetomidine (DEX) is an α2-adrenergic agonist. It decreases the levels of norepinephrine release, resulting in a reduction of postsynaptic adrenergic activity. In the present study, the effects of DEX on postpartum bleeding-induced multiple organ dysfunction syndrome (BMODS) were studied in rats in which BMODS was induced by the combination of hypotension and clamping of the superior mesenteric artery. We evaluated the role of dexmedetomidine (DEX) in cytokine release during postpartum BMODS in rats. In summary, the present study demonstrated that DEX administration reduced IFN-r and IL-4 release and decreased lung injury during postpartum BMODS. It is possible that DEX administration decreased inflammatory cytokine production in BMODS by inhibiting inflammation and free radical release by leukocytes independent of the DEX dose.